A longitudinal multicase study about the board-game format of an educational self-talk intervention - Mathas, V.; Solomon-Turay, P.; Hatzigeorgiadis, A.; Hardy, J.; Latinjak, A. T. (The Sport Psychologist, 2024)
This study explored goal-directed self-talk and its optimization through educational self-talk interventions, focusing on a novel sports-oriented board-game intervention. Examining a practitioner`s experiences and diverse participant profiles, including an elite tennis player, a recreational athlete, a football referee, and a tennis coach, the research employed four in-depth case studies. A unique aspect of this study involved intentional control transfer from practitioner to client, documented through a practitioner diary and postintervention interviews. Participants generally expressed appreciation for the intervention; however, the coach`s case necessitated bespoke adjustments, underscoring the importance of contextual sensitivity in applied practice. The educational self-talk intervention reportedly facilitated the analytical deconstruction of challenges, enhancing self-regulation through goal-directed self-talk. The study underscored the pedagogical merit of the board game and observed a substantive transfer of control from practitioner to participant over the intervention`s longitudinal trajectory. Detailed recommendations have been crafted for practitioners to implement the educational self-talk intervention effectively in their practice.